Development of STEM-Based Learning Devices for Science Teachers Oriented on Students' Creative Thinking Skills - Faiq Makhdum Noor; Dody Rahayu Prasetyo; Salic-Hairulla, Monera A.; Andriawan Saputra; Tania Indra Dwi Safira (Universitas Negeri Semarang, 2025)
This study aims to develop STEM (Science, Technology, Engineering, and Mathematics)-based science learning devices that are oriented towards improving students' creative thinking skills. The research method used is the ADDIE development model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were teachers and students of class VIIA MTs NU Nurussalam. At the analysis stage, data was obtained regarding teachers' needs for STEM-based learning devices that are integrated with simple learning KITs based on inorganic waste. At the design stage, learning devices were compiled including teaching modules, LKPD, evaluation questions, and KIT Gecoseed (Gardening with Ecoseedling), which uses used bottles and simple planting media. This device also integrates the context of Sustainable Development Goals (SDGs) goal 15, namely maintaining terrestrial ecosystems. Implementation is carried out through socialization activities and implementation of learning in the classroom. Evaluation is carried out through questionnaires to teachers and students. The results showed that the STEM-based learning device was well received, with 93% of teachers stating that the device was easy to implement and 87% of students stating that learning was fun and motivated them to think creatively. In addition, students' creative thinking skills increased after learning as indicated by the N-Gain Score of 0.7 with a high category. This study concludes that the STEM-based learning device developed is effective in increasing students' engagement and creative thinking skills, and is relevant to be applied in science learning at the madrasah level.